2002
DOI: 10.1212/wnl.58.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Frontocortical N -acetylaspartate reduction associated with long-term IV heroin use

Abstract: To examine possible metabolic frontal lobe alterations in i.v. heroin-dependent patients with different histories of concomitant substance use, N-acetylaspartate (NAA), a putative marker of neuronal viability, was measured by (1)H-MRS. Compared with controls, NAA levels in patients were reduced by 7% in gray matter (p = 0.015) but not in white matter. To what extent comorbid conditions or substance use, including alcohol, contributed to these frontocortical metabolic changes remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 10 publications
2
17
1
Order By: Relevance
“…21,45 The only study to date that used proton MRS in an opiate-dependent subjects found NAA decreases of similar magnitude in frontal grey matter. 46 It is interesting that unlike previous work in healthy individuals, the NAA metabolite reductions we identified were unrelated to behaviour measures of task performance and dACC physiological activity. [47][48][49] This would seem to suggest that, in opiate-addicted subjects, BOLD activity is not dependent on NAA levels, perhaps because the NAA reductions are dissociated from neuronal loss.…”
Section: Discussioncontrasting
confidence: 72%
“…21,45 The only study to date that used proton MRS in an opiate-dependent subjects found NAA decreases of similar magnitude in frontal grey matter. 46 It is interesting that unlike previous work in healthy individuals, the NAA metabolite reductions we identified were unrelated to behaviour measures of task performance and dACC physiological activity. [47][48][49] This would seem to suggest that, in opiate-addicted subjects, BOLD activity is not dependent on NAA levels, perhaps because the NAA reductions are dissociated from neuronal loss.…”
Section: Discussioncontrasting
confidence: 72%
“…At the gross structure level, opiate-dependent addicts exhibited decreased gray matter density in both the prefrontal and the temporal cortex [41] . At the cellular level, neuron damage in the bilateral frontal cortex have been reported [42,43] . fMRI studies have found that heroin addicts had a hypoactivation of PFC which involves response inhibition [14,15] , whereby addicts exhibited decreased N2d amplitudes on fronto-central scalp sites compared with the controls.…”
Section: Potential Reasons For the Abnormal Processmentioning
confidence: 99%
“…Response inhibition recruits a neural network including the frontal regions and the non-frontal regions, such as the orbital frontal cortex (OFC), the dorsolateral prefrontal cortex (DLPFC), the ventrolateral prefrontal cortex (VLPFC), the anterior cingulate cortex (ACC),and the parietal, temporal, and striatal lobes [11] . Structural magnetic resonance imaging studies showed that prefrontal and temporal gray matter density decreases in chronic heroin addicts [12,13] . Furthermore, function magnetic resonance imaging (fMRI) results indicated that the decreased activity of the frontal and parietal regions was observed not only in current heroin addicts [14] but also among abstinent [15] in the response inhibition task.…”
mentioning
confidence: 99%
“…Methamphetamine (47) and heroin (48) are both associated with reductions of NAA levels, and reductions observed with ecstasy (49) are correlated with scores on working memory testing (50).…”
Section: N-acetyl Aspartate (Naa)mentioning
confidence: 99%